MASALAH YANG DIHADAPI MAHASISWA PSTM UM KONSENTRASI TARI PADA MATA KULIAH TARI BALI DI TENGAH PANDEMI COVID-19 - ika wahyu widyawati (Jurusan Seni dan Desain, Fakultas Sastra, Universitas Negeri Malang, 2021)
The learning process is currently carried out with online media because during this pandemic by the government is encouraged to reduce being in crowded places. This kind of learning process is done at home to break the chain of spread of COVID-19. With this increasingly advanced technology, it can be used as a medium in the learning process. However, there are also shortcomings with this kind of learning model. Most of the students prefer to learn online, especially if they get balinese dance practice materials. Because it will be very effective and understandable material rather than learning online. In addition, there are perceived complaints that more and more tasks while studying online. But not a few also among students, who like to learn through online because learning like this is quite practical and fun. This kind of condition is felt by students of the Dance and Music Arts Education Program of Malang State University in the vocational courses of Balinese Dance.